2001
DOI: 10.3177/jnsv.47.147
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, Serum Cholesterol Concentration and Their Related Factors in Urban and Rural Elderly of Ho Chi Minh City.

Abstract: SummaryIn Vietnam, information about blood pressure, serum lipids and their factors is limited. To obtain some of this information, a cross sectional nutrition survey was carried out in an urban and rural area of Ho Chi Minh City with 217 participants aged 60-69y (148 females and 69 males). Anthropometry and blood pressure were measured. For three consecutive weekdays, 24h dietary recalls were performed. Single 24h urine was collected for sodium and potassium analysis. A fasting blood sample was taken and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
7
2
Order By: Relevance
“…In our current study, the percentage of subjects with a BMI > 24 kg/m 2 was only 10.9% in Hei Yi Zhuang and 20.6% in Han, suggesting that the effect of BMI on blood pressure was small in both nationalities. However, in the present study we found that the prevalence of hypertension was positively correlated with TG in Hei Yi Zhuang, and positively correlated with TC in Han (23).…”
Section: Discussioncontrasting
confidence: 77%
“…In our current study, the percentage of subjects with a BMI > 24 kg/m 2 was only 10.9% in Hei Yi Zhuang and 20.6% in Han, suggesting that the effect of BMI on blood pressure was small in both nationalities. However, in the present study we found that the prevalence of hypertension was positively correlated with TG in Hei Yi Zhuang, and positively correlated with TC in Han (23).…”
Section: Discussioncontrasting
confidence: 77%
“…In our current study, only 10.2% of the Hei Yi Zhuang and 22.7% of the Han subjects had a BMI 1 24 kg/m 2 , suggesting that the effect of BMI on the prevalence of hypertension is weak in both ethnic groups. However, the present study shows that the prevalence of hypertension was positively correlated with TGs in Hei Yi Zhuang and with TC in Han [51] . The relationship between hypertension and hyperlipidemia remains relatively poorly understood.…”
Section: Discussionmentioning
confidence: 41%
“…Moreover, diets high in trans fatty acids, which are abundantly present in processed foods, caused abdominal obesity and insulin resistance (Kavanagh, Jones et al 2007). Similar effects of nutrient poor, calorically dense diets have been demonstrated in humans (Hodge, Dowse et al 1995;Tran, Komatsu et al 2001;Hursting, Lavigne et al 2003;Newby, Muller et al 2003). In humans, caloric restriction also retards aging and reduces rates of chronic disease; therefore, this simple measure may also help to reduce risk for neurodegeneration (Qin, Chachich et al 2006;Kim, Nguyen et al 2007;Wang, Fivecoat et al 2010).…”
Section: Western Diet and Insulin/igf Resistance Mediated Neurodegenementioning
confidence: 70%